THE CORRELATION BETWEEN STUDENTS’ ACTION VERBS MASTERY AND THEIR WRITING ABILITY IN PROCEDURE TEXTS AT NINTH GRADE SMPN 4 TAMBANG - Regi Muliana (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2026)
Writing is one of the essential skills that students must master in learning English, especially in writing procedure texts that require clear and systematic instructions. Action verbs play an important role in procedure texts because they indicate the steps or actions that must be performed. However, many students still face difficulties in using action verbs when writing procedural texts. This study aims to determine the correlation between students’ mastery of action verbs and their writing ability in procedure texts at the ninth grade of SMPN 4 Tambang. This research used a quantitative correlational design. The population of this research consisted of 62 ninth-grade students. The data were collected through two instruments: a multiple-choice test to measure students’ mastery of action verbs and a writing test to measure students’ ability in writing procedure texts. The data were analyzed using the Pearson Product Moment correlation with the help of SPSS 25.0. The results of the analysis showed that the correlation coefficient (r) was 0.680 with a significance value of 0.000, which is lower than 0.05. This indicates that there is a positive and statistically significant correlation between students’ mastery of action verbs and their writing ability in procedure texts. Therefore, students who have better mastery of action verbs tend to have better writing ability in procedure texts. These findings suggest that English teachers should pay more attention to teaching action verbs as part of vocabulary development to improve students’ writing skills.